2008
DOI: 10.1021/la8002756
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Temperature-Responsive Poly(N-isopropyl acrylamide) Graft Copolymers: from Triggered Association to Gelation

Abstract: In this work temperature-triggered association and gel formation within aqueous solutions of a new family of cationic poly( N-isopropyl acrylamide) (PNIPAm) graft copolymers have been investigated. Five copolymers were synthesized using aqueous atom transfer radical polymerization (ATRP) involving a macroinitiator based on quaternarized N, N-dimethylaminoethyl methacrylate units (DMA+). The PDMA+) x - g-(PNIPAmn)y copolymers have x and y values that originate from the macroinitiator; values for n correspond to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
81
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(85 citation statements)
references
References 40 publications
1
81
3
Order By: Relevance
“…However, within the range of concentrations assessed (up to 2.5 wt%), the strength of the structure was observed to decrease substantially with decreasing concentration. Examples of this type of study are rarely reported in the literature, but Liu et al [42] reported that the minimum gel concentration (resistant to inversion with 'vigorous shaking by the hand') of quaternized poly(DMAEMA-graft-NIPAM)s was 6.4 wt%. The concentration reported for cell culture studies is typically 5 -10 wt% [19,20,26].…”
Section: Characterization Of Thermoresponsive Polymersmentioning
confidence: 99%
“…However, within the range of concentrations assessed (up to 2.5 wt%), the strength of the structure was observed to decrease substantially with decreasing concentration. Examples of this type of study are rarely reported in the literature, but Liu et al [42] reported that the minimum gel concentration (resistant to inversion with 'vigorous shaking by the hand') of quaternized poly(DMAEMA-graft-NIPAM)s was 6.4 wt%. The concentration reported for cell culture studies is typically 5 -10 wt% [19,20,26].…”
Section: Characterization Of Thermoresponsive Polymersmentioning
confidence: 99%
“…x -g-ðPNIPAm n Þ y copolymers has been described in detail elsewhere [1]. A brief description is given below.…”
Section: Copolymer Synthesismentioning
confidence: 99%
“…The copolymers were prepared by aqueous ATRP using a macroinitiator, MI. The MIs were prepared from [1] poly(DMA-stat-HEMA) poly(N,N-dimethylaminoethyl methacrylate-stat-hydroxyethyl methacrylate) followed by its conversion to a quaternized, isobutyrate functionalized version using the method established by Chen and Armes [34]. To prepare PDMA þ…”
Section: Copolymer Synthesismentioning
confidence: 99%
See 2 more Smart Citations